Pediatric Reconstruction of Full-Thickness Dog Bite Scalp Avulsion with a Combination of Acellular and Matrix Products: A Case Report - Francesca Grussu; Guido Ciprandi; Federico Lo Torto; Diego Ribuffo; Mario Zama (Medicina)
The reconstruction of large full-thickness scalp injuries represents a great challenge in pediatric plastic surgery. Epidermal–dermal substitutes come to the rescue when traditional surgical strategies are not suitable. Recently, the new Integra MicroMatrix UBM particulate has arisen on the market. This is an extracellular matrix derived from the porcine urinary bladder matrix (UBM) in which the particulate structure provides close contact to the wound bed. We present the concomitant application of Integra DRT and MicroMatrix for the reconstruction of a full-thickness subtotal scalp defect in a child mauled by a dog.